Climate-Smart Small Ruminant Innovations (Smart Pack) Implemented by Universities - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The International Center for Agricultural Research in the Dry Areas (ICARDA), in partnership with ILRI and Ethiopian NARs, has been pilot-testing climate-smart integrated small ruminant value chain development innovations (Smart Pack) over many years in Ethiopia. Smart pack encompasses innovations such as sheep and goat genetics, improved feeding, gender capacity development and transformation, herd health package and marketing. Results of the evaluation of the implementation of the Smart Pack have revealed that such packages are technically feasible to implement and result in the improvement of the livelihood of the resource-poor. Therefore, they are ready to scale. Consequently, we worked with Ethiopian Universities to see if they could assist in the scaling of the innovations in nearby villages to meet their teaching, research and community service mandate. Our sustained effort has resulted in 16 Universities investing in establishing 42 breeding cooperatives involved in implementing Smart Pack.